Selection of common bean lines for calcium use efficiency - Domingues, Lucas; Ribeiro, Nerinéia; Andriolo, Jerônimo; Possobom, Micheli Thaise; Zemolin, Allan Emanoel (Revista Ciência Agronômica, 2014)
The study of the calcium use efficiency in common bean is unprecedented. Therefore, the objectives of this work were to evaluate the genetic variability of common bean lines for plant growth and grain yield characters, the calcium accumulation in different plant tissues at low and high calcium availabilities, and to select common bean lines with high calcium use efficiency and responsive to the calcium application by different indices. Twelve common bean lines were supplied with a nutrient solution at low (1.10 mmol L-1) and high (3.85 mmol L-1) calcium concentration and were evaluated. The L 15 line reached the higher values of dry mass of shoot, number of pods and grains per plant, number of grains per pod and grain yield at the low calcium concentration. Calcium accumulation in tissues was, on average, higher in leaves, followed by stems, pods and grains. The L 175 and L 159 lines have higher calcium concentration in grains (> 1.1 g kg-1 MS), regardless of the calcium concentration supplied to plants. The L15 line is efficient in calcium use. The L 221 and L 159 lines are responsive to the calcium application in the rooting medium.